1997
DOI: 10.1088/0953-2048/10/6/005
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of flux pinning by thermo-mechanical treatment of Bi-2223/Ag superconducting tapes

Abstract: Measurements of the transport critical current in a magnetic field (H), hysteresis loops and a.c. susceptibility were performed on Bi-2223/Ag tapes that were subjected to different degrees of mechanical deformation and subsequently sintered. against H for some of the tapes was also measured at different stages of thermo-mechanical treatment. All the measurements (the field of the peak of the pinning force, the irreversibility field obtained from hysteresis loops and the temperature of the peak of a.c. suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
(50 reference statements)
0
4
0
1
Order By: Relevance
“…It was found that the flux pinning increases only after a pressed Bi-2223/Ag tape is further sintered. This indicates that imperfectly healed microcracks, reminiscent of low-angle tilt boundaries, may be the pinning centre responsible for the reported increase in pinning by mechanical deformation [134,135].…”
Section: Pinning By Point Defects and Nonuniformitiesmentioning
confidence: 90%
“…It was found that the flux pinning increases only after a pressed Bi-2223/Ag tape is further sintered. This indicates that imperfectly healed microcracks, reminiscent of low-angle tilt boundaries, may be the pinning centre responsible for the reported increase in pinning by mechanical deformation [134,135].…”
Section: Pinning By Point Defects and Nonuniformitiesmentioning
confidence: 90%
“…Weak links and flux pinning decide the critical current density (J c ) of Ag/Bi-2223 powder-in-tube (PIT) tapes. In order to improve the zero-field J c (B = 0) in Bi-2223/Ag tapes, grain connectivity must be improved and this is best achieved by introducing a high c-axial texture and clean (defect-free) grain boundaries [1][2][3][4][5][6][7][8][9][10][11][12]. To enhance the in-field J c of Bi-2223 composites, improvements in the capacity to pin magnetic flux, the introduction of splayed columnar defects, dislocations and secondary phase precipitates are thought to enhance flux pinning [2,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported [1][2][3] that the zero-field J c can be improved by reducing the 2212 content and nonsuperconducting phases [10,11] and obtaining better grain connectivity and grain alignment via cold [2,11] or hot [4,10] pressing, in the belief that a high zero-field J c (B = 0) implies a higher in-field critical current density J c (B) [1,3]. However, J c (B) can be improved by the introduction of irradiation pinning centres [8,9], slow cooling [12] and introduction of mechanical handling [7]. In this paper, we reported that grain connectivity was significantly improved by hot pressing in Bi-2223/Ag multifilamentary tapes.…”
Section: Introductionmentioning
confidence: 99%
“…³äêðèòòÿ âèñîêîòåìïåðàòóðíèõ íàäïðî-â³äíèê³â ³ ïðîãðåñ òåõíîëîã³é âèãîòîâëåííÿ êð³îåëåêòðîííèõ ì³êðîñòðóêòóð ïðèâåëî äî ïðàêòè÷íîãî âèêîðèñòàííÿ ñòâîðåíèõ íà îñ-íîâ³ åôåêò³â Äaeîçåôñîíà êâàíòîâèõ åëåêòðî-ííèõ êîì³ðîê ïàì'ÿò³ [1][2][3][4]. Ïåðñïåêòèâí³ñòü ¿õ çàñòîñóâàííÿ â êîìï'þòåðí³é òåõí³ö³ âè-çíà÷àºòüñÿ âèñîêîþ øâèäêî䳺þ ïîð³âíÿíî ³ç òðàäèö³éíèìè íàï³âïðîâ³äíèêîâèìè åëåìåí-òàìè.…”
Section: âñòóïunclassified